TEACHING VOCABULARY USING DIGITAL MEDIA DURING COVID-19 PANDEMIC - Al Idris Saichun Nizar (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The pandemic made a way of teaching to adapt. Offline teaching turned into online teaching. Teaching vocabulary is very important even in pandemic situations. This study aims to find out how to teach vocabulary during pandemic at UNISMA, which includes what strategies are used in teaching vocabulary and what media are used in teaching vocabulary, to find out what problems occur when teaching vocabulary in a pandemic and how the solution is. The subject of this research is a lecturer at the University of Islam Malang Faculty of Teacher Training and Education English Education Department, who teaches reading 2. The findings of this research are the vocabulary teaching process used synonyms, the media used are google classrooms, google meets , WhatsApp, and PowerPoint slides, the problems faced, such as lack of students' motivation in learning because teaching activity is online based. Problems with teaching techniques are general issues such as difficulties in operating online applications, high costs, and poor signals. For the solution, the lecturer suggested a way to replace the applications used in teaching into applications that are more fun and more easy to use.Keywords: Teaching Strategies, Vocabulary, Online Media, Pandemic